2011
DOI: 10.1016/j.acvd.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Initial hospital pulse pressure and cardiovascular outcomes in acute coronary syndrome

Abstract: In ACS, all blood pressure variables were significantly correlated. Low PP was an independent predictor for stroke and mortality in overall ACS. Although PP was not superior to systolic blood pressure, only low PP was an independent predictor for recurrent ischaemia in NSTE-ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…Similar results were also found by Davidovic et al., who primarily analysed the influence of tachycardia on the outcome of patients with STEMI, but also found that higher systolic blood pressure was associated with better outcome , and El‐Menyar et al., who found that lower pulse‐pressure was associated with higher mortality after ACS .…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were also found by Davidovic et al., who primarily analysed the influence of tachycardia on the outcome of patients with STEMI, but also found that higher systolic blood pressure was associated with better outcome , and El‐Menyar et al., who found that lower pulse‐pressure was associated with higher mortality after ACS .…”
Section: Discussionsupporting
confidence: 83%
“…Patients with LVEDP >18 mm Hg had increased hazard ratios (95% confidence intervals) for death at 30 days (2.00; 1.20 to 3.33, P = 0.007) and 2 years (1.57; 1.12 to 2.21, P = 0.009) compared to patients with LVEDP ≤ 18 mm Hg . El‐Menyar found that pulse pressure correlated with SBP and mean arterial pressure and that a pulse pressure ≤ 30 mm Hg was associated with excess mortality in a study of more than 2500 patients with STEMI .…”
Section: Discussionmentioning
confidence: 99%
“…Invasive hemodynamic measurements at the time of PPCI have the theoretical advantage of better reflecting both left ventricular loading conditions and afterload than do non‐invasive assessments. Various parameters including an elevated left ventricular end diastolic pressure (LVEDP), low SBP, and low pulse pressure have each been independently associated with a higher mortality rate . Numerous studies have shown that Killip class is a robust predictor of outcomes suggesting that integration of left ventricular filling pressures and SBP provides important prognostic information but it is unclear whether the use of directly measured hemodynamic variables would increase the predictive accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with LVEDP >18 mm Hg had increased hazard ratios (95% confidence intervals) for death at 30 days (2.00; 1.20–3.33, P = 0.007) and 2 years (1.57; 1.12–2.21, P = 0.009) compared to patients with LVEDP ≤18 mm Hg. El‐Menyar et al found that a PP ≤30 mm Hg was associated with excess mortality in a study of more than 2,500 patients with STEMI . We previously reported that an SBP/LVEDP ratio ≤4 greatly increased the risk of in‐hospital mortality in STEMI patients undergoing PPCI and Tesak et al found that SBP/LVEDP predicted 30‐day mortality in STEMI patients with an optimal cut‐off of 4.4 .…”
Section: Discussionmentioning
confidence: 96%